Super (a; d)-H-Antimagic Total Covering of Triangular Cycle Ladder Graph for Developing Ciphertext - Irma Azizah; Dafik Dafik; Slamin Slamin (jcgant, 2020)
A (a; d)-H-antimagic total covering is a total labeling dari V (G) [ E(G) to integer number f1; 2; 3; :::; jV (G) [ E(G)jg with condition, every subgraph A inP P PG isomorphic with subgraph H A = v2V (A) (v) + e2E(A) (e) on arith-metic sequence. A graph containing the labeling called super (a; d)-H-antimagic total covering. Furthermore , f (v)gv2V = f1; :::; jV jg, is called graph super H antimagic. In this research used triangular Cycle Ladder Graph T CLn of con-nective to developing ciphertext. Key Word : Super H antimagic total selimut, Triangular Cycle Ladder Graph T CLn, Ciphertexts.